FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PENDAPATAN NELAYAN BURUH DI KELURAHAN LEATO SELATAN KECAMATAN DUMBO RAYA KOTA GORONTALO - Alkatiri, Ramlah; Adjung, Septiana Elistiawati (Universitas Muhammadiyah Gorontalo, 2024)
The aim of this research is to identify the partial influence of several factors on the income level of working fishermen in Leato Selatan Subdistrict, Gorontalo City. The research method used is a quantitative approach with a descriptive type. Data collection techniques are carried out through questionnaires, observation and documentation. The research results show that: 1) Partially, price has a significant influence on the income level of labor fishermen in South Leato Village, Gorontalo City. This is proven by the tcount value of 2.898 which exceeds the ttable value of 2.571, with a significant value of 0.008, where the significant value is smaller than 0.05. 2) Partially, operational costs also have a positive and significant influence on the income level of labor fishermen in South Leato Village, Gorontalo City. The tcount value of 2.880 exceeds the ttable value of 2.571, with a significant value of 0.030, which is also smaller than 0.05. 3) Partially, wages also have a positive and significant influence on the income level of working fishermen in Leato Selatan Subdistrict, Gorontalo City. The tcount value of 2.886 exceeds the ttable value of 2.571, with a significant value of 0.028, which is also smaller than 0.05. 4) Simultaneously, the independent variables in this model as a whole have an effect on the dependent variable. Through testing, a probability value obtained is greater than the α value (0.001 < 0.05). The calculation results show that the Fcount value is 7.156, which is greater than the Ftable value of 6.94.